Metodología del aprendizaje para atender las necesidades académicas de los estudiantes con dificultad en lecto-escritura de la escuela de educación básica “Dr. Francisco Martínez Aguirre” del cantón Vinces, provincia de los Ríos - Zurita Smith, Daisy Liseth (2017)
This research project was to determine the importance of the methodology of the learning for the difficulty in reading-writing in the students of third year of basic education of the "Dr. Francisco Martínez Aguirre "Vinces Canton, Province of Los Ríos. It is very difficult for students to learn to read and write, starting from the shortcomings detected through the application of the instrument in the surveys in the present research to parents of students, students and teachers, analyzing the answers can determine the main causes in the shortcomings in the difficulty in reading-writing. With the didactic guide, it is intended to be applied in order to satisfy the expectations that arose during its management and, consequently, the group under study, acquire pedagogical elements of great value that allow him to understand the importance of reading and writing both in his learning process and in his academic performance and personal growth.